Encuesta sobre el Poder Judicial - Bustos Gisbert, Rafael; Delgado del Rincón, Luis E.; Figueruelo Burrieza, Ángela; López Aguilar, Juan Fernando; López Guerra, Luis María; Murillo de la Cueva, Pablo Lucas; Rosado Iglesias , María Gema; Serra Cristóbal, Rosario (Teoría y Realidad Constitucional, 2022)
Encuesta sobre el Poder Judicial